Knowledge management in public administration of education, science and technology in Northeast Brazil - Cavalcanti, Gustavo Moura; Brito, Lydia Maria Pinto; Castro, Ahiram Brunni Cartaxo de; Silva, Arthur William Pereira da (Regae: Revista de Gestão e Avaliação Educacional, 2021)
The objective of this study was to analyze the managers’ view on education about Knowledge Management in a public institution of education, science and technology in Northeastern Brazil. This is a basic case study investigation and a qualitative research. The reference frameworks used were the knowledge management diagnosis, suggested by Bukowitz and Williams (2002), and the indexes recommended by Brito, Oliveira and Castro (2012). The results showed that Knowledge Management is in a maturation process in the institution researched. The Obtain and Use sections support the positive performance in the tactic processes, and the Build/Keep and Disposal sections support the strategic process. On the other hand, the results indicate that the organization should invest in the development of the sections Learn, which deals with the connection between organizational strategy and the learning derived from everyday actions, and in the Contribute section of the tactical process, as the organization must encourage its professionals contribute with the knowledge you have. In the strategic process, the organization should invest in the Evaluate section of the DGC, as it is up to the organization to identify new forms of organizational capital that can add value so that it can adapt to changes in the macro environment. Key-words: knowledge management; public administration; education; science; technology.